98 Sarcopenia: a case study in how the phenomenon of overdiagnosis is generated. (20th August 2018) - Bülow, Jacob; Holm, Lars; Brodersen, John
Abstract : Objectives: In 1989 the term Sarcopenia was introduced to describe the phenomenon of age-related loss of muscle mass. From 2010 to 2014 six consensus definitions were presented based on the previous two decades of research within the field of sarcopenia. Despite the fact that loosing muscle mass originally was seen as a normal process of ageing, it was classified as a disease in 2016 and dedicated its own ICD-10 code. The arguments for classifying age-related loss of muscle mass as a disease put forth by the consensus papers and leading scientist in the research field of sarcopenia are sparse and use tautological reasoning in its attempt to legitimate this transformation. The purpose of the study is firstly to clarify whether or not Sarcopenia is another case of overdiagnosis due to overdefinition, and if so, secondly to give new insight in how the phenomena of overdiagnosis arise. Method: The analysis in this study is based on an historical approach to the scientific literature on Sarcopenia. An understanding of the transformation of the phenomenon from normal to pathological will be approached by analysing the conceptualization of sarcopenia in cornerstones articles in the research field of sarcopenia chronological from the introduction of the concept through the different decades up until its admission in ICD-10. The current consensus definitions of Sarcopenia and the argumentation for its admission in ICD-10 will be compared to the general understanding of the concept of overdiagnosis, to clarify whether or not this new disease is a case of overdiagnosis. Results: During the decade of 1990 the transformation of sarcopenia from a normal to a pathological condition started. The phenomenon was made guilty by association to both mortality and decreased physical function, with the problem that over 50% of the population over 80 years would be considered as sarcopenic. From 2000 a decreased physical function became a criterion, to narrow down the amount of patients categorized with sarcopenia, in the effort of legitimizing it as an independent pathological phenomenon. It culminated in admission of an ICD-10 code in 2016, which put Sarcopenia in line with other age-related diseases such as osteoporosis, diabetes and hypertension. Comparing the consensus definitions with the concept of overdiagnosis, Sarcopenia seems to be a case of overdefinition. The change of the conception of Sarcopenia from a normal to a pathological process is a lowering of the threshold of what we in general categorize as disease. Conclusions: With the rewarding of an independent ICD-10 code and its acceptance as a disease in the geriatric research field, Sarcopenia has become another example of the increase in overdiagnosis in especially the modern western societies. Despite differences in historical development the definition of Sarcopenia shows great similarities with other phenomena such as osteoporosis and hypertension where overdiagnosis is present. The historical analysis of the transformation of Sarcopenia gives insights into how phenomena, otherwise considered as completely normal and compatible with life, can change its ontological status into a treatment demanding disease. Further investigating of its comparability to other age related phenomena could possibly elucidate further mechanism behind the appearance of overdiagnosis. This could contribute to the understanding of the phenomenon of overdiagnosis and how to prevent further expansion of this unfortunate development.